Business communication design: creativity, strategies, and solutions - Angell, Pamela A. (Maidenhead : McGraw Hill Education, 2007)
Emphasizes the role of critical and creative thinking in the communication process. This book offers a model for message design that focuses on the needs of the people involved in the communication and the circumstances of the message. It addresses the variety of communication options that modern workers face.
1 The Basics -- 2 How Business Communicates -- 3 Creating Effective Messages -- 4 Listening: A Silent Hero -- 5 Creating and Using Meaning -- 6 Designing Messages with Words -- 7 Designing Oral Presentations -- 8 Business Writing Design -- 9 Direct and Indirect Communication Strategies -- 10 The Business of Reports: Informal and Formal Report Writing -- 11 Writing Strategies for Reports and Proposals -- 12 Culture: Inside and Out -- 13 Interpersonal and Collaborative Messages -- 14 The Business of Change and Conflict -- 15 Creating a Career and Designing Resumes -- 16 Interviewing to Get the Job -- 17 Creativity and Visual Design
Includes bibliographical references.
Keywords: BUSINESS COMMUNICATIONS